What does community forestry mean in a devolved Great Britain?. (1st June 2009) - Lawrence, A; Anglezarke, B; Frost, B; Nolan, P; Owen, R
Community forestry is evolving in Great Britain across a variety of social and environmental contexts. Following devolution, England, Scotland and Wales have separate forest strategies. In England community forestry often refers to management of new and existing woodland in areas of urban regeneration for public benefit. Social activism and policy changes in Scotland have led to a twofold model of urban regeneration, and community ownership and enterprise in rural areas. In Wales community forestry has developed through efforts led by rural communities and project funding, with results now incorporated into a new forest strategy. After outlining the historical context of forestry in Great Britain the paper examines developments within each country, and compares them with aspects of community forestry identified globally. The paper highlights the fit of community forestry with wider policy goals including urban and rural regeneration, alleviating social deprivation, and partnership between government agencies, non-government organisations and communities. It indicates the diversity of tenure arrangements, motivations and project support for community forestry, and challenges including sustainability and wider networking and capacity building.